Low Intrinsic Aerobic Capacity Limits Recovery Response to Hindlimb Ischemia - Granier, Elizabeth; Zakari, Madaniah O.; Alsahly, Musaad B.; Koch, Lauren G.; Britton, Steven; Katwa, Laxmansa C.; Lust, Robert M. (Frontiers in Cardiovascular Medicine, 2021)
In this study we determined the influence of intrinsic exercise capacity on the vascular adaptive responses to hind limb ischemia. High Capacity Running, HCR; Low Capacity Running, LCR, rats were used to assess intrinsic aerobic capacity effects on adaptive responses to ischemia. Methods: Muscle samples from both ischemic and non-ischemic limb in both strains were compared, histologically for the muscle-capillary relationship, and functionally using microspheres to track blood flow and muscle stimulation to test fatigability. PCR was used to identify the differences in gene expression between the phenotypes following occlusive ischemia. Results: Prior to ligation, there were not significant differences between the phenotypes in the exhaustion time with high frequency pacing. Following ligation, LCR decreased significantly in the exhaustion time compare with HCRs (437 ± 47 vs. 824 ± 56, p <0.001). The immediate decrease in flow was significantly more severe in LCRs than HCRs (52.5% vs 37.8%, p < 0.001). VEGF, eNOS, and ANG2 (but not ANG1) gene expression were decreased in LCRs vs HCRs before occlusion, and increased significantly in LCRs 14D after occlusion, but not in HCRs. LCR capillary density (CD) was significantly lower at all time points after occlusion (LCR 7D = 564.76 ± 40.5, LCR 14D= 507.48 ± 54.2, both p < 0.05 vs HCR for respective time point). NCAF increased significantly in HCR & LCR in response to ischemia. Summary: These results suggest that LCR confers increased risk for ischemic injury and is subject to delayed and less effective adaptive response to ischemic stress.